2020
DOI: 10.1089/dia.2019.0444
|View full text |Cite
|
Sign up to set email alerts
|

Parent Preferences for Delaying Insulin Dependence in Children at Risk of Stage III Type 1 Diabetes

Abstract: Background: Autoantibody screening in type 1 diabetes (T1D) may reduce the chances of potentially lifethreatening diabetic ketoacidosis (DKA) at diagnosis by allowing individuals at risk of progression to more actively monitor for and/or manage progression to insulin dependence. We investigated parents' preferences for treatments to delay the onset of insulin dependence in children who are at high risk of developing Stage III T1D. Methods: A web-based survey (n = 1501) was administered to a stratified sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The duration of benefit for a disease-modifying therapy and side effects were combined in one attribute, limiting insights from this study into how respondents might trade off duration of benefit and side effects. However, in a DCE survey conducted by DiSantostefano et al ( 35 ) among parents to elicit preferences for treatments to delay insulin dependence in children, duration of benefit, risk of serious infection, and chance of nausea were included. The results of that study demonstrated parents’ risk tolerance for treatments to delay insulin dependence and acceptable trade-offs between duration of benefit and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of benefit for a disease-modifying therapy and side effects were combined in one attribute, limiting insights from this study into how respondents might trade off duration of benefit and side effects. However, in a DCE survey conducted by DiSantostefano et al ( 35 ) among parents to elicit preferences for treatments to delay insulin dependence in children, duration of benefit, risk of serious infection, and chance of nausea were included. The results of that study demonstrated parents’ risk tolerance for treatments to delay insulin dependence and acceptable trade-offs between duration of benefit and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The study sample included 1501 parents: 600 who had a child with T1D and 901 who did not. The mean age was 40 years, 64% were female, and approximately 55% had a 4-year college degree or more (see DiSantostefano et al 21 for more details on the sample).…”
Section: Resultsmentioning
confidence: 99%
“…A DCE was administered online to 1501 adult parents in the United States with children currently under the age of 18 years. The DCE aimed to elicit the parents’ preferences for treatments that delayed the onset of T1D in children who had tested positive for the autoantibodies associated with T1D (see DiSantostefano et al 21 for study details). Respondents chose between two hypothetical interception treatments or an opt out (monitoring only, no treatment) in a series of experimentally designed choice questions.…”
Section: Methodsmentioning
confidence: 99%
“…Preventive treatment preference studies in at-risk and general public samples have been conducted in other disease areas including genetic testing for colorectal cancer screening and delaying onset of type 1 diabetes mellitus in children. 13 , 45 Generally, studies suggest that efficacy is the most important attribute across samples and that the ranks of the most and least important attributes are similar across groups; however, the relative weights, MAR, and predicted uptake could be quite different across at-risk and general public samples. For example, in colorectal cancer screening, the relative importance weights differed between the screened population compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In a study of treatment delaying the onset of type 1 diabetes mellitus, the MAR were higher among children of parents whose children had type 1 diabetes mellitus versus those who did not have a child with type 1 diabetes. 45 Also, psychological distance (e.g., perceived risk of getting the condition, experience with the condition) strongly influenced preferences. 13 More research is needed to compare preferences, engagement, and quality of data from different at-risk populations (general public v. individuals at higher risk) in the disease prevention context for RA and other conditions.…”
Section: Discussionmentioning
confidence: 99%